Preventing cardiovascular disease in Africa – we must act now - Volmink, Jimmy (SA Heart Journal, 2017)
A tsunami of non-communicable diseases (NCDs) such as cardiovascular disease, diabetes, chronic respiratory disease and cancer is threatening to engulf Africa. Globally, the vast majority of NCD deaths occur in low- and middle-income countries placing a significant burden on the world’s poor. In 2004, one-quarter of all deaths in sub-Saharan Africa were due to NCDs; by 2030 this figure will rise to almost half.(2) Age-standardised death rates from NCDs are already higher in some African countries (the Democratic Republic of the Congo, Nigeria, Ethiopia and South Africa) than in high income countries.(3) NCDs share several modifiable risk factors, in particular unhealthy diets, tobacco use, physical inactivity and excessive use of alcohol. This presents an opportunity for action to limit the profound human and economic costs of NCDs predicted for African countries already reeling under the weight of infectious diseases and injuries. A concerted, multi-sectoral and sustained effort will, however, be required which must be implemented without further delay.